Biocrust impacts on dryland soil water balance: A path toward the whole picture. (12th September 2022) - Li, Shenglong; Bowker, Matthew A.; Xiao, Bo
Abstract: As a crucial living feature inhabiting the soil–atmosphere boundary, biocrusts play a vital role in liquid water or vapor transport through surface soil and thus have strong effects on soil water regimes. However, it remains unclear how biocrusts affect annual or multiyear soil water budgets through the regulation of evaporation outputs and non‐rainfall water (NRW) or infiltration inputs. Thus, we used automated microlysimeters to continually investigate the differences in evaporation and NRW rates between moss‐dominated biocrusts and bare soil at 0–5 cm depth for 2 years. The upper 30 cm of soil moisture ( θ ) and water storage ( W ) of bare soil and biocrusts were also monitored. Our results showed that the daily evaporation rate ( E ) of biocrusts was 17% higher than bare soil. Especially after rainfall events, biocrusts had higher E and larger cumulative evaporation than bare soil. Besides, the daily NRW of biocrusts averaged 15% higher than bare soil over 2 years. Furthermore, biocrusts increased θ by 11%–76% at 0–10 cm depth but decreased θ by 32%–56% at 20–30 cm depth in comparison to bare soil, and they subsequently decreased W by 20% at 0–30 cm depth. Summarized annually, the NRW amount of biocrusts was 19% higher than bare soil, but at the same time, the cumulative evaporation of biocrusts was also 19% higher than bare soil. Finally, biocrusts resulted in more water loss at shallow depth through evaporation and lessened total W throughout 0–30 cm depth of soil. These findings demonstrate that although biocrusts input more NRW into surface soil, these water inputs partially offset their intensified evaporation. Given that all rainfall water infiltrates into the soil in our study system, our findings indicate that biocrusts may have an overall negative effect on soil water balance there, while at the same time increasing water storage and availability of the deeper soil underlying biocrusts. Abstract : Over 2 years of measurements, the cumulative evaporation of moss‐dominated biocrusts was 19% higher than bare soil, while the non‐rainfall water (NRW) amount of biocrusts was also 19% higher than bare soil. Biocrusts further increased near‐surface soil moisture but decreased overall soil water storage by 20% within 0–30 cm layer in comparison to bare soil. Briefly, although biocrusts input more NRW into surface soil, these water inputs partially offset their intensified evaporation, leading to an overall negative effect of biocrusts on soil water storage.